Employee Absence: An Organizational Perspective - Jacob Kjær Eskildsen; Anders Frederiksen; Ann-Kristina Løkke (Institute of Labor Economics (IZA), 2018)
We study employee absence in Danish organizations. In contrast to Steers and Rhodes (1978), who stress the importance of individual and organizational characteristics in shaping employees' motivation to attend work, we show that absence is predominantly an individualized phenomenon. Because the within-group variation in absence clearly dominates the between-group variation in absence, we argue that companies need to invoke individualized policies to reduce employee absence and demonstrate that HR Analytics is a useful tool in the process; policies targeting particular employee groups such as women or senior workers are inefficient. An additional intriguing finding is that incentives (through promotions and dismissals) are linked to individual absence.
Keywords: M12; M54; 330; absence; absenteeism; HR Analytics; person-effects; incentives; personnel management